Effect of rapid cefpodoxime disk screening for early detection of third-generation cephalosporin resistance in Escherichia coli and Klebsiella pneumoniae bacteremia - Mikiyasu Sakai; Takamasa Sakai; Yuki Nagata; Hiroko Komai; Yoshio Miyake; Toshitaka Watariguchi; Atsushi Kawabata; Fumiko Ohtsu (BMC, 2023)
Abstract Background Several methods have been reported for detecting resistance genes or phenotypic testing on the day of positive blood culture in Escherichia coli or Klebsiella pneumoniae bacteremia. However, some facilities have not introduced these methods because of costs or other reasons. Toyota Kosei Hospital introduced cefpodoxime (CPDX) rapid screening on May 7, 2018, to enable early detection of third-generation cephalosporin resistance. In this study, we aimed to evaluate the effects of intervention with an Antimicrobial Stewardship Team using CPDX rapid screening. Methods Cefotaxime (CTX)-resistant E. coli or K. pneumoniae bacteremia cases were selected retrospectively and divided into two groups: the pre-CPDX screening (June 1, 2015, to May 6, 2018) and CPDX screening groups (July 7, 2018, to August 31, 2021). The primary outcome was the proportion of cases in which modifications were made to the administration of susceptible antimicrobial agents within 24 h of blood culture-positive reports. Results Overall, 63 patients in the pre-CPDX screening group and 84 patients in the CPDX screening group were eligible for analysis. The proportion of patients who modified to susceptible antimicrobial agents within 24 h of blood culture-positive reports was significantly increased in the CPDX screening group compared to that in the pre-CPDX screening group (6.3% vs. 22.6%, p = 0.010). Conclusion The results demonstrated that in CTX-resistant E. coli or K. pneumoniae bacteremia, CPDX rapid screening increased the proportion of early initiation of appropriate antimicrobial agents.